2019
DOI: 10.1103/physrevlett.122.187401
|View full text |Cite
|
Sign up to set email alerts
|

Exciton-Phonon Coupling in the Ultraviolet Absorption and Emission Spectra of Bulk Hexagonal Boron Nitride

Abstract: We present an ab initio method to calculate phonon-assisted absorption and emission spectra in the presence of strong excitonic effects. We apply the method to bulk hexagonal BN which has an indirect band gap and is known for its strong luminescence in the UV range. We first analyse the excitons at the wave vector q of the indirect gap. The coupling of these excitons with the various phonon modes at q is expressed in terms of a product of the mean square displacement of the atoms and the second derivative of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 53 publications
1
75
0
Order By: Relevance
“…In the case of a real system with many vibrational modes, our strategy is to exploit the same mechanism leading to Eq. (27), by leveraging the cancellation between 'similar' modes, i.e. modes of the same branch at adjacent q-points.…”
Section: A the Simplest Case: One Vibrational Modementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of a real system with many vibrational modes, our strategy is to exploit the same mechanism leading to Eq. (27), by leveraging the cancellation between 'similar' modes, i.e. modes of the same branch at adjacent q-points.…”
Section: A the Simplest Case: One Vibrational Modementioning
confidence: 99%
“…This problem is becoming increasingly important as we strive to achieve close quantitative agreement between ab initio calculations and experimental data. Furthermore this problem underpins calculations of many important properties, from temperature-dependent optical absorption [24][25][26] and emission spectra [27] to temperature-dependent * fgiustino@oden.utexas.edu transport coefficients [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that the band gap of MLBN is direct at K in reciprocal space [40] while the fundamental band gap of bulk hBN is indirect between M and K points of the first Brillouin zone [41,42]. The high internal quantum efficiency is correlated to the strong exciton-phonon coupling with an efficient and fast phonon emission that relaxes the k-dependent selection rule traditionally preventing indirect band gap semiconductors to strongly emit light via intrinsic processes [43][44][45][46][47][48]. This intriguing specificity of hBN is currently under active study, including the physics of the free and bound excitons.…”
Section: The Early Daysmentioning
confidence: 99%
“…The c-axis polarized B 1g mode gives rise to the optical branches labelled as ZO 1 and ZO 3 , corresponding to the low-energy and high-energy modes respectively, and the A 2u mode gives rise to the ZO 2 branch. In Figure 10, the different phonon branches are labelled using this systematic scheme [48,74,92], which will allow us to unambiguously identify the phonons that participate in the phonon-assisted emissions. There are three pairs of branches, namely TA and TO 1 , LA and LO 1 , and TO 2 and TO 3 that derive from different zone centre modes and they are non-degenerate at finite q although the branches are very close in frequency within each pair.…”
Section: Bulk Single Crystalsmentioning
confidence: 99%
“…We compare our theoretical results with the observed thermal evolution of SiC band edges, and discuss our findings in the light of high temperature SiC electronics and defect qubits operation.Electron-phonon interaction impacts a large variety of fundamental materials properties [1], from the critical temperature of superconductors to the zero-point renormalization and the temperature dependence of the electronic energy bands, from the electronic band gaps [2][3][4][5][6] to the thermal evolution of the optical spectra and excitonic lifetimes [7][8][9]. In addition the electron-phonon coupling contributes to the optical absorption and emission in indirect gap semiconductors [10][11][12], determines the electronic carrier mobility of semiconductors [13], the carrier relaxation rates [14], the distortion of band structures and phonon dispersion giving rise to kinks and Kohn anomalies in photoemission [15].Direct observation of the temperature evolution of individual bands over a wide region of temperatures is not straightforward. Optical techniques are capable of measuring band gaps, and not the absolute values of the valence band maximum (VBM) and the conduction band minimum (CBM) separately.…”
mentioning
confidence: 99%